The Effect Of Classical Music Therapy On The Level Of Depression Among Schizophrenia Patients In Soeprapto Mental Hospital, Bengkulu Province - Surya Direja, Ade Herman; Juksen, Loren; Sunarsih, Sunarsih (Chakra Brahmanda Lentera Institute, 2021)
Background: Patients with mental disorders experience disturbances in mental function, which include emotions, thoughts, behavior, motivation, self-perception, and perception, which causes a decrease in all mental functions, especially interests, and motivations so that it interferes with a person in the process of living in society. One o the most common mental disorders is schizophrenia. This study aims to study the effect of classical music therapy on depression level in schizophrenic patients at the Soeprapto Mental Hospital, Bengkulu Province Methods: The design in this study used a pre-experimental design. The design form of a pre-experimental study is